2021
DOI: 10.3389/fnut.2021.772220
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of Crackers Substitution of Wheat Flour With Jellyfish

Abstract: The objective of this study was to investigate the possibility of using jellyfish (Lobonema smithii) for the production of nutritionally improved crackers. In this study, ground jellyfish were incorporated into different levels (20, 30, and 40%) to replace wheat flour in cracker formula. Physicochemical characteristics (linear expansion, hardness, and color) and sensory quality of the developed crackers were examined and compared with control crackers. The crackers with jellyfish were found significantly darke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Among the different formulations of crackers variation 3 (C3), 30% of watermelon rind flour substitution has the highest overall acceptability. A similar study has shown that cookies formulated with 30% watermelon rind flour incorporation had the highest overall acceptability (8.23) [20] . The variation with the highest overall acceptability, C3 has been tested for nutrients and phytochemicals.…”
Section: Organoleptic Evaluation Of the Formulated Crackersmentioning
confidence: 77%
See 1 more Smart Citation
“…Among the different formulations of crackers variation 3 (C3), 30% of watermelon rind flour substitution has the highest overall acceptability. A similar study has shown that cookies formulated with 30% watermelon rind flour incorporation had the highest overall acceptability (8.23) [20] . The variation with the highest overall acceptability, C3 has been tested for nutrients and phytochemicals.…”
Section: Organoleptic Evaluation Of the Formulated Crackersmentioning
confidence: 77%
“…A way to reduce the glycemic index in bakery products would be the partial substitution of wheat flour with flours, rich in indigestible carbohydrates. Literature search showed that the blends of acha and pigeon pea [15] , corn silk [16] , red onion skin [17] , pea peel [18] , defatted coconut flour [19] , jelly fish [20] , Hibiscus sabdariffa calyxes' residue [21] , pumpkin seed flour [22] , etc. had been used as prospective ingredients to formulate value added crackers.In this regard, watermelon rind, as a source of fibre and nutraceuticals, is used in this study as a means to reduce the rate of absorption of glucose from crackers.…”
mentioning
confidence: 99%
“…The expansion was reduced because less water was trapped in the network of starch gel. According to Maisont et al ( 43 ), the lower the degree of cracker expansion, the fewer air cells formed and trapped, and thus the lower the cracker hardness ( 43 ).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, nuggets prepared with 10, 20, and 30% jellyfish replacing catfish meat obtained an average liking of 3.5–3.8 on a five-point hedonic scale, corresponding to an evaluation between neutral (3) and like (4) [ 28 ]. Finally, crackers made by replacing wheat flour content with ground jellyfish (20–40% w / w of total wheat) reached a mean liking score of 6.1–6.4 on a seven-point hedonic (1 = extremely dislike, 7 = extremely like) [ 29 ].…”
Section: Discussionmentioning
confidence: 99%